DINAMIKA DUAL CARIER FAMILY ATAU WORK-FAMILY CONFLICT PADA IBU YANG BEKERJA SEBAGAI PENGAMBIL KEPUTUSAN ATAU TOP MANAGER/LEADER DI LINGKUNGAN KERJANYA - Hj. DARMAWATI DARMAWATI (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2015)
The results showed that the cause of the work family confict on women working sourced either from work or family. Source of work that working time arrangements and job content experienced by respondents BD, DM, AR, NA, MI and RN. While the source of the family is characteristic of the situation of house holds, which have dependents who require more attention, such as the respondent BD, DM, AR as well as the limitations/lack of help to complete the household responsibilities as experienced by respondents NA. In order to overcome work family confict facing working women use a combination of coping strategies that focus on problem (problem-based coping) and focuses on the emotions (emotion-based coping). Problem-based coping is done by taking action to modify, avoid or reduce conficts like hiring a maid Household, prioritize, and maintain communication with other family members has been carried out by all respondents. While emotion-based coping is done by trying to eliminate the uncomfortable feeling due to the confict. This coping strategy is done privately (solitary coping) as diligently worship (made by BD, DM, AR and NA) and involve others (social coping) as share with friends and family and also do a hobby or personal pleasure.